Plantar pressure differences between cases with symptoms of clinically diagnosed chronic exertional compartment syndrome and asymptomatic controls. (December 2017) - Roberts, Andrew; Hulse, David; Bennett, Alexander N.; Dixon, Sharon
Abstract: Background: Anterior chronic exertional compartment syndrome of the leg has been hypothesised to develop due to excessive muscle activity and foot pronation. Plantar pressure variables related to lower limb muscle activity and foot type may therefore provide insight into this condition. Methods: 70 male cases and 70 asymptomatic controls participated. A clinical diagnosis was established from typical symptoms, with clinical examination excluding other pathologies. Plantar pressure variables during walking, hypothesised to be related to foot type, toe extensor activity or had shown predictive validity for general exercise-related lower leg pain, were extracted. Findings: Cases were shorter in height (mean difference 2.4 cm), had greater body mass (mean difference 4.4 kg) and had reduced ankle dorsiflexion range of motion than controls (mean difference 1.5 cm). Plantar pressure variables indicative of foot-type and toe extensor activity did not differ between groups ( P  > 0.05). The magnitude of medial forefoot loading was the strongest plantar pressure predictor of the presence of chronic exertional compartment syndrome (Odds ratio:0.87, P  = 0.005). There was also some evidence of greater lateral heel loading at 5% of stance time ( P  = 0.049–0.054). Interpretation: The lack of association with foottype-related and toe extensor activity-related plantar pressure variables suggest that these are not risk factors for the development of chronic exertional compartment syndrome, contrary to earlier hypotheses. The greater lateral to medial loading could theoretically represent increased Tibialis anterior muscle activity at heel strike but a subsequent loss of control as the ankle is lowered. Future studies directly investigating muscle activity and function are now required. Highlights: Cases were shorter in height and had greater body mass than controls. No evidence for differences in foot-type or anterior compartment muscle activity Cases had greater medial forefoot loading.